Nominal Suffixes in William Shakespeare's Romeo and Juliet - Ni Komang Tri Aningsih; I Gusti Bagus Wahyu Nugraha Putra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This research focuses on analyzing the derivational nominal suffixes found in William Shakespeare’s novel Romeo and Juliet (Wordsworth Classics). The study aims to identify what types of derivational nominal suffixes appear in the novel and to find out which type is the most frequently used. Using a descriptive qualitative method, the researcher collected data by reading the novel carefully and selecting words that contain derivational nominal suffixes. The collected words were then grouped into three categories based on their base forms: nouns formed from verbs, nouns formed from adjectives, and nouns formed from other nouns. The analysis found a total of 161 words with derivational nominal suffixes. The most dominant type is nouns formed from verbs, which appeared 90 times (55.90%), followed by nouns formed from adjectives with 45 occurrences (27.95%), and nouns formed from nouns with 26 occurrences (16.15%). This study helps to better understand how word formation works in English, especially in literary works, and may serve as a helpful reference for students and researchers who are interested in studying English morphology and vocabulary development. Keywords: derivational suffixes, nominal suffixes, word formation, morphology, Romeo and Juliet